Denis Johnston’s Revisionist Theatre - Kopschitz Bastos, Beatriz (ABEI Journal, 2003)
Denis Johnston’s first and last plays are, in essence, historical plays. The Old Lady Says ‘No!’(1929) portrays the leader of the 1803 Rising, Robert Emmet. The Scythe and The Sunset (1958) is an Easter Rising play. The object of this article is to consider in what ways these plays can be read not only as historical, but, moreover, as revisionist plays.